Consumer Buyer Behaviour of Two Wheelers in Tirunelveli City, Tamil Nadu - Haneef, M. Abdul; Gnanadhas, M. Edwin; Karim, B. A.Abdul (Indian Journal of Marketing, 2006)
Everybody in this world is a consumer. We need a variety of goods and services right from our birth to death. All consumers are buyers and all buyers are not consumers. Then who are the consumer buyers and how they behave while purchasing a particular product is very important for marketers. Consumer buyer behaviour refers to the buying behaviour of final consumers - individuals and households who buy goods and services for personal consumption. Walter says that buyer behaviour is the process whereby individuals decide what, when, where, how and from whom to purchase goods and services. Consumer behaviour is influenced strongly by cultural, social, personal and psychological factors. Cultural factors include the set of basic values, perceptions, wants and behaviour learned by a member of society from family and other important institutions. The social factors include consumer's family, small group, social roles and status. The personal characteristics such as buyer's age, life cycle stage, occupation, economic situation and life style influence a buyer's decision. A person's buying choices are further influenced by four major psychological factors: Motivation, Perception, Learning, Beliefs and Attitudes.